The implementation of a “safety officer” program: an innovative approach to improve infection prevention and control practices in Ethiopia - Woldeamanuel, Solomon Abebe; Thumba, Linda; Gabul, Warku Habte; Ahmed, Kowsar; Mekonnen, Gebeyehu Asire; Tarekegn, Blen; Nhanala, Aristides Cabral; Kent, Paula S.; Ashengo, Tigistu Adamu; Wu, Albert W.; Dagoye, Damtew Woldemariam; Curless, Melanie S.; et al. (Frontiers in Public Health, 2024)
Background Effective infection prevention and control (IPC) was central to keeping healthcare workers (HCWs) safe during the COVID-19 pandemic. However, as the pandemic continued, the maintenance of high-quality IPC practices waned, placing HCWs at increased risk of infection. A COVID-19 Safety Officer (SO) program was piloted by the United States Agency for International Development (USAID)-funded Reaching Impact, Saturation and Epidemic Control (RISE) project across two health facilities in Ethiopia, which trained clinical and non-clinical HCWs on IPC protocols to promote safe practices in patient care areas. We sought to evaluate the implementation and effectiveness of the SO program in improving IPC practices within the clinical setting. Methods This is a post-implementation evaluation of the SO program, implemented in two hospitals in Ethiopia between May 2022 and December 2022. Participants completed a 4-day course on COVID-19 epidemiology, IPC, safety communication, and learning theory as a part of the Training of Trainers component (n = 23), and were posted in clinical wards to provide staff training and support to maintain IPC protocols. The program was evaluated at 6 months using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework. Effectiveness was measured using direct observation of IPC practices across intervention sites. Implementation outcomes were measured using surveys and qualitative interviews to capture training cascade, knowledge, comfort, acceptability, and maintenance. Results Participants were able to cascade training to an additional 167 clinical (67.6%) and 80 non-clinical (32.3%) staff across both sites. Direct observation of clinical staff at 6 months showed that 95% (59/62) wore at least a surgical mask with patients and were compliant with masking and/or distancing protocol. Clinical interviews revealed that SOs contributed to increased perceived comfort with screening and isolation procedures and environmental cleaning procedures. Conclusion The SO training program was widely adopted, and effective in improving the implementation and comfort of maintaining IPC practices in clinical settings.